Obtención de ácido cítrico a partir de yacón mediante fermentación utilizando la cepa de Aspergillus niger CMPUJH002 (2021)
Yacón is root rich in fructooligosaccharides together with simple sugars (sucrose, fructose, glucose), however, its use has been limited to local gastronomic consumption, which is why its possible industrial uses are not taken advantage of. For this reason, this study evaluated some of the process variables for its use as a possible substrate for obtaining citric acid through fermentation with Aspergillus niger. Taking into account the type of carbohydrates present in the yacón, the development of the project was divided into three parts: 1. The obtaining and characterization of the yacón extract where a series of treatments were carried out adapting the tuber to the required conditions, 2. The fermentation process of the yacón hydrolysate with Aspergillus niger; on each of the experimental phases the yields were analyzed, thus finding that the amount of reducing sugars through the hydrolysis process was 12.185g/L for the hydrolyzed fresh extract and 8.165g/L for the hydrolyzed matured extract. The fresh yacón hydrolysate was used since the final reducing sugars were considerably higher.